BMP-2 releasing mineral-coated microparticle-integrated hydrogel system for enhanced bone regeneration - Xu, Hongwei; Luo, Huanhuan; Chen, Jiayu; Chen, Gang; Yu, Xiaohua; Ye, Zhaoming (Frontiers in Bioengineering and Biotechnology, 2023)
Large bone defects (LBD) caused by trauma, infection, and tumor resection remain a significant clinical challenge. Although therapeutic agents such as bone morphogenetic protein-2 (BMP-2) has shown substantial potency in various clinical scenario, their uncontrollable release kinetics has raised considerable concerns from clinical side. Mineral coated microparticle (MCM) has shown its excellent biologics loading and delivery potential due to its superior protein binding capacity and controllable degradation behaviors, thus it is conceivable that MCM can be combined with hydrogel systems to enable optimized BMP-2 delivery for LBD healing. Herein, BMP-2 was immobilized on MCMs via electrostatic interaction between its side chains with coating surface. Subsequently, MCM@BMP-2 is anchored into a hydrogel by the cross-linking of chitosan (CS) and polyethylene glycol (PEG). This microparticle-hydrogel system exhibits good biocompatibility, excellent vascularization, together with the sustained release of BMP-2 in the bone defect. Furthermore, it is observed that this microspherehydrogel system accelerates the bone formation by promoting the expression of osteogenic related proteins such as RUNX2, osteopontin and osteocalcin in bone marrow mesenchymal stem cells (BMSC). Thus, this newly developed multifunctional microparticle-hydrogel system with vascularization, osteogenesis, and sustained release of growth factor demonstrates an effective therapeutic strategy towards LBD.